CHANGE MANAGEMENT AND ORGANISATIONAL TRANSFORMATION: A STUDY OF NEM INSURANCE PLC (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This study titled change management and organisational transformation observed that we are living in seriously turbulent and dynamic times and that most businesses in developing economies are still lackadaisical about diligent change management for the purpose of positively guided transformation. Thus, it majorly examined the relationships between change management and business transformation in Nigeria, particularly in the insurance industry. The study hinged majorly on Planned Behaviour/Reasoned Action theory had a population of 700 employees from across the different locations in Nigeria. Subsequently, it adopted the Dillman (2000) simplified sample size determination technique to arrive at a sample size of 249. The study adopted a multistage sampling technique in selecting and electronically administering Google-form questionnaire on the sample size. With a response rate of 73.09 percent, the study analysed the data using the ANOVA and multiple regression statistical techniques. The findings revealed that change management is significantly and positively related to business transformation particularly that of the case study. Consequently, the study recommended that contemporary businesses (no matter the size) should always diligently manage change for positively enhanced transformation as changes are inevitable, rapid, and complex in contemporary times. Specific relevant change management components should be adopted at all times for transformation in related specific areas as shown by this study